ACTIVE, CAPABLE, AND POTENTIALLY ACTIVE FAULTS - A PALEOSEISMIC PERSPECTIVE - Machette M.N. (My University, 2000)
Maps of faults (geologically defined source zones) may portray seismic hazards in a wide range of completeness depending on which types of faults are shown. Three fault terms - active, capable, and potential - are used in a variety of ways for different reasons or applications. Nevertheless, to be useful for seismic-hazards analysis, fault maps should encompass a time interval that includes several earthquake cycles. For example, if the common recurrence in an area is 20,000-50,000 years, then maps should include faults that are 50,000-100,000 years old (two to five typical earthquake cycles), thus allowing for temporal variability in slip rate and recurrence intervals. Conversely, in more active areas such as plate boundaries, maps showing faults that are <10,000 years old should include those with at least 2 to as many as 20 paleoearthquakes. For the International Lithosphere Programs' Task Group II-2 Project on Major Active Faults of the World our maps and database will show five age categories and four slip rate categories that allow one to select differing time spans and activity rates for seismic-hazard analysis depending on tectonic regime. The maps are accompanied by a database that describes evidence for Quaternary faulting, geomorphic expression, and paleoseismic parameters (slip rate, recurrence interval and time of most recent surface faulting). These maps and databases provide an inventory of faults that would be defined as active, capable, and potentially active for seismic-hazard assessments.
Keywords: Quaternary; Cenozoic::Quaternary; Кайнозой::Четвертичная